Management and Awareness on Health Hazards of Household Waste: A Community based study - Manandhar, Naresh; Ataullah, Syed; Raj, Rishav; Chakraborty, Pallabi; Adhikari, Supriya Raya; Sharma, Deeksha (Birat Journal of Health Sciences, 2021)
Introduction:  Waste is physical things or unwanted materials that are of no use to the human beings.1 Waste management is the activities and actions required to manage waste from its inception to its final disposal.Objectives: The objective of study is to assess the management and awareness on health hazards of household waste in a community of Khopasi, Kavrepalanchowk district.Methodology:  The study design was descriptive cross-sectional and it was conducted from 10th November to 15th November 2019 at Khopasi, Kavrepalanchowk using convenience sampling technique in 281 households. The statistical package for social sciences (SPSS) version 20 was used for data entry and analysis. Descriptive statistics like frequency, mean, percentage etc was calculated.Results:  The mean age of 281 respondents was 44.89 years. Similarly 43.8% of respondents considered waste management as a major issue and 84.3% had knowledge about health hazards due to improper waste disposal. Forty-seven percentages of the respondents disposed of their waste through waste collecting vehicle, 26% by burning, 17% threw their waste by riverbank, and 9% threw their waste indiscriminately in the surrounding area.Conclusion: The majority of respondents were aware about adverse effect on their health due to improper waste disposal. However the knowledge of waste management program is poor. They throw waste in the river bank or indiscriminately in open places.